Design and implementation of a single phase active power filter - Mkhize, Michael (Department of Electrical Engineering, 2015)
Various active filter solutions have been proposed in recent years {I], {2], and are still being widely investigated today. This thesis discusses the design and implementation of the shunt AP F topology.